PLN BALI INTERNAL COMMUNICATION STRATEGY TO ENCOURAGE THE USE OF ELECTRIC MOTORCYCLES AMONG EMPLOYEES - Made Eka Tirtayana , (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
The world has been focusing on global warming and climate change issues in recent decades. The transportation sector, particularly fossil-fueled vehicles, contributes significantly to greenhouse gas emissions in Indonesia. PT PLN (Persero) Bali, as a state-owned electricity company, has a crucial role in supporting the government's electric vehicle program. This study aims to analyze the internal communication strategies implemented by PLN Bali to encourage employees to adopt electric motorcycles. The research employs a qualitative method with a phenomenological approach to understand the subjective experiences of PLN Bali employees regarding internal communication strategies and the use of electric motorcycles. Data were collected through in-depth interviews with policy makers, employees who have purchased and used electric vehicles, and those who have not. The findings reveal that PLN Bali has designed and implemented internal communication strategies, including the involvement of influencers, the use of internal media channels, and the formation of electric motorcycle communities in each unit. These strategies have been effective in increasing awareness, understanding, and interest in electric motorcycles among employees. However, there are still obstacles in implementation, such as concerns about the risks and limitations of electric motorcycles and the lack of supporting infrastructure.